Lyotropic Liquid Crystalline Nanostructures as Drug Delivery Systems and Vaccine Platforms - Maria Chountoulesi; Stergios Pispas; Ioulia K. Tseti; Costas Demetzos (MDPI AG, 2022)
Lyotropic liquid crystals result from the self-assembly process of amphiphilic molecules, such as lipids, into water, being organized in different mesophases. The non-lamellar formed mesophases, such as bicontinuous cubic (cubosomes) and inverse hexagonal (hexosomes), attract great scientific interest in the field of pharmaceutical nanotechnology. In the present review, an overview of the engineering and characterization of non-lamellar lyotropic liquid crystalline nanosystems (LLCN) is provided, focusing on their advantages as drug delivery nanocarriers and innovative vaccine platforms. It is described that non-lamellar LLCN can be utilized as drug delivery nanosystems, as well as for protein, peptide, and nucleic acid delivery. They exhibit major advantages, including stimuli-responsive properties for the "on demand" drug release delivery and the ability for controlled release by manipulating their internal conformation properties and their administration by different routes. Moreover, non-lamellar LLCN exhibit unique adjuvant properties to activate the immune system, being ideal for the development of novel vaccines. This review outlines the recent advances in lipid-based liquid crystalline technology and highlights the unique features of such systems, with a hopeful scope to contribute to the rational design of future nanosystems.